ANALISIS PENGARUH GAYA KEPEMIMPINAN OTORITER KEPALA DESA TERHADAP KINERJA APARATUR DESA PANGKALAN BULIAN BATANG HARI LEKO - Usailan Oemar; Rully Alamsyah; Reki Arisandi (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2018)
Authoritarian leadership is if power or authority, mostly absolute to leader or if the leader adheres to a centralized system of authority. Decision making and wisdom are only determined by the leader himself, subordinates are not included to give suggestion, idea, and consideration in the decision making process. His / her leadership just focused on increasing employee work productivity and And less attention to employees' feeling and walfare. The influence of authoritarian leadership style has affected toward the village aparatus job performance At Pangkalan Bulian Kecamatan Batang Hari Leko Musi Banyuasin regency showed low correlation (35.1%) and positive toward the village aparatus job performance at PangkalanBulianKecamatanBatangHarilekoMusiBanyuasin regency, because r value is in the range of 0.20 – 0.399. It is also proven by seeing at R Sequare that is 0.123 that is information that 12.3% of employees' job performance variable(Y) is affected by authoritarian leadership style variable (X) while The rest 87.7% is explained by other factors. Hypothesis test result (t-test) between authoritarian leadership style toward employees job performance also showed that Ho Is rejected and Ha is accepted it means that authoritarian leadership style has affected toward village aparatus' job performance Pangkalan Bulian Kecamatan Batang Hari Leko Musi Banyuasin regency with A level of significance<0.05 that is 0.001.